(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Non-traumatic headaches are a common presentation in emergency services. A non-contrast computed tomography (NCCT) scan of the head is done when there is suspicion of intracranial abnormalities. Such intracranial abnormalities are indicated by "red flag" signs. This study aimed to determine the prevalence of intracranial abnormalities in patients with non-traumatic headaches and its association with the red flag signs. Method: A total of 106 patients presenting with a non-traumatic headache to the emergency services of TUTH from Aug 2019 to Aug 2020, who underwent head CT were included in the study. The association of head CT positivity with the presence of red flag signs was studied by bivariate analysis using the chi-square test or Fisher exact test. Result: Among 106 patients, 46(43.4%) were male and the rest were female. The mean age of the patient was 43.69+17.46. All the patients who had positive findings in head CT had at least one red flag sign. Out of 16 red flag signs included in this study, 10 signs showed a significant association (p<0.05) with head CT positivity. These are sudden onset of headache, age of onset >50 years, significant change in pattern or severity of headache, “worst headache ever”, vomiting, neck stiffness, seizures, altered sensorium, papilledema, and focal neurological deficits. Conclusion: Red flag signs of headache are helpful to determine whether head CT is needed or not to look for significant intracranial abnormalities in a patient presenting with non-traumatic headache in an emergency.